The role of fiscal instruments in environmental policy - Katri Kosonen; Gaëtan J.A. Nicodème (Center for Economic Studies and ifo Institute (CESifo), 2009)
Environmental protection is one of Europe's key values. The EU has set clear policy objectives to achieve its environmental goals. The EU has favoured market-based instruments, among which fiscal instruments to tackle the climate change problem. This paper takes a policy-making perspective and provides an overview of key issues on the role of fiscal instruments in energy and environmental policies. It describes fiscal instruments as cost-effective means to promote environmental goals and highlights in which cases taxes and other types of fiscal instruments can usefully complement each other to achieve environmental target.
Keywords: H23; Q38; Q48; Q58; 330; taxation; environmental policy; VAT; fiscal incentives; Ökosteuer; Umweltabgabe; Energiesteuer; Energiesparen; Steuerbegünstigung; Umweltpolitik; Wirkungsanalyse; EU-Umweltpolitik